Plano de alta de enfermagem da pessoa idosa pós Acidente Vascular Cerebral do hospital para o domicílio - Coêlho, Wender Gonçalves (2024)
Introduction: Stroke is a disease that ranks as the second leading cause of death worldwide and the leading cause of disability, with one in four people experiencing this complication at some point in their lives. It is more prevalent in the elderly population, who often require hospitalization. Readmissions are costly and undesirable, and elderly individuals are more vulnerable to hospitalization, necessitating transitional care to maintain continuity of care. Therefore, a Care Transition Model is crucial for the seamless transfer of care from the hospital to the home. Objective: To describe the care transition of elderly individuals after a stroke from the hospital to the home. Method: The study was conducted in three stages: The first stage involved a scoping review plan following the methodology recommended by the Joanna Briggs Institute. The Population, Concept, and Context strategy was used for searching the databases. The second stage consisted of a methodological study to develop a nursing discharge plan for the care transition of elderly individuals after a stroke from the hospital to the home, and the third stage involved the validation of the discharge plan. The analysis included descriptive and similarity analysis, using word clouds and the Content Validity Ratio index. Results: Out of the 1,378 studies, 30 were selected for full-text reading, resulting in 12 articles published between 2013 and 2023, including three qualitative, eight quantitative, and one mixed-method study. Two chapters from gray literature books were included to complement the sample, resulting in a total of 14 studies addressing the topic. The findings from the scoping review served as the theoretical framework for developing the discharge plan. After obtaining informed consent via a Google Form, the plan was sent via email to a panel of 13 expert judges in the field of gerontological/neurological nursing, who evaluated the clarity, theoretical relevance, and practical pertinence of the 60 content evaluation items using the Iramuteq software. Descriptive evaluation and the Content Validity Ratio index were employed. The clarity and theoretical relevance indicators ranged from 0.846 to 1.000. In terms of practical pertinence, all items had Content Validity Ratio values of 1.000, indicating adequacy. Conclusion: The scoping review highlighted a lack of knowledge regarding discharge protocols for individuals affected by stroke. There is a need for detailed approaches, emphasizing the establishment of individualized discharge plans and care. The content analysis of the scoping review, conducted using the Iramuteq software, revealed five categories, and the data were validated by 13 expert judges, with a Content Validity Ratio exceeding 0.846. The study demonstrated the urgency of care transition for elderly individuals after a stroke in the country, and it is the responsibility of nurses and their teams to develop this practice to enhance care and facilitate prompt rehabilitation. The importance of these practices is evident in the continuity of home care, aiming to reduce or eliminate potential sequelae. To contribute to the development and application at the hospital level, a discharge plan for elderly individuals after a stroke, transitioning from the hospital to the home, was proposed as a technical product.